2021
DOI: 10.35808/ersj/2510
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of CSR/ESG on the Cost of Capital: A Case Study of US Companies

Abstract: Purpose:The paper identifies the direction and strength of the relationship between individual ESG elements (and ESG as a whole) and the weighted average cost of capital, the cost of equity, and debt. The research was based on US market company data from the Thomson Reuters Eikon database. Some modifications have been applied to the survey methodology compared to that previously used in the literature, making it possible to present comprehensive and more congruent results. Identifying the direction and strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…They reported evidence showing that environmental performance reduces cost of debt. In similar vein, Piechocka-Kaluzna et al (2021) reported significant negative correlation between ESG and its sub dimensions and cost of finance. Huu Anh et al (2020) reported evidence that firms disclosing more accounting information related to environmental issues tend to have lower cost of finance than those who do not.…”
Section: Literature Reviewmentioning
confidence: 69%
“…They reported evidence showing that environmental performance reduces cost of debt. In similar vein, Piechocka-Kaluzna et al (2021) reported significant negative correlation between ESG and its sub dimensions and cost of finance. Huu Anh et al (2020) reported evidence that firms disclosing more accounting information related to environmental issues tend to have lower cost of finance than those who do not.…”
Section: Literature Reviewmentioning
confidence: 69%
“…В останні роки процес та чинники зміни / збереження вартості капіталів і вартості бізнесу досліджувала низка науковців, серед яких: J. Martinez-Ferrero, I. Garcia-Sanchez [11], J. Martinez-Ferrero, E. Ruiz-Barbadillo, M. Guidi [12], A. Piechocka-Kaluzna, A. Tluczak, P. Lopatka [19], D. Marchiori, R. Rodrigues, S. Popadiuk, E. Mainardes [10], Z. Mengke, H. Yan, J. Yifan [13], S. Noor, A. Saeed, M. Baloch, M. Awais [16], X. Wang, J. Yu [24], K. Elmawazini, I. Chkir, F. Mrad, H. Rjiba [4]. Названі вчені відзначили зокрема такі фактори, як соціальна відповідальність бізнесу, інновації та диджиталізація.…”
Section: огляд літературиunclassified